MULTICULTURAL ISLAMIC EDUCATION IN AZYUMARDI AZRA'S THOUGHT - Rusmin Nuryadin Situmeang; Muhammad Qorib; Zailani (International Journal of Teaching and Learning, 2025)
This research aims to analyze multicultural Islamic education according to Azyumardi Azra's views, To analyze and obtain information on Azyumardi Azra's views on multicultural Islamic education and its relevance to national education, To analyze the relevance of multicultural Islamic education to modern education. The method in this study is qualitative with a figure study approach and the type of research used is (library reserch), which is research carried out using literature (literature), both in the form of papers, relevant scientific papers, books, notes, and reports on the results of previous research. The results of the study provide information about azyumardi's thinking on multicultural Islamic education, its relevance to education to national education and its relevance to modern education. The conclusion of this study is how multicultural Islam is explored through Azyumardi's thought, its relevance to national education and modern education so that the community, both from educators, students, students and other elements of society can understand about the social that comes from various different backgrounds who must live in equality and mutual respect in order to create a safe education,  peace and tranquility without any discriminatory treatment from any party.